2023
DOI: 10.3389/fsufs.2023.1098642
|View full text |Cite
|
Sign up to set email alerts
|

Productive efficiency of beef cattle production in Botswana: a latent class stochastic meta-frontier analysis

Abstract: IntroductionEfficiency in food production is crucial for sustainable agriculture in developing countries. This paper contributes to the existing literature by presenting an innovative approach to modeling productive efficiency in beef cattle production. Treating farm performance across regions as unobserved heterogeneity, we determine technical efficiency of beef cattle production in Botswana. We aim to shed light on the factors influencing efficiency in this sector.MethodsThe study utilized block-level data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Based on evidence of farming systems' heterogeneity of in the study area (Bernard et al 2010;MAEP, 2019;Akpatcho et al 2022), this study considers that production technologies of the farms are not homogenous. Studies found evidence that results of technical efficiency could be misleading if production technology heterogeneity is not considered (Sauer et al 2013;Bahta et al 2018). Although heterogeneity can be modelled using several methodological approaches.…”
Section: Empirical Endogenous Stochastic Production Frontier Modelmentioning
confidence: 99%
“…Based on evidence of farming systems' heterogeneity of in the study area (Bernard et al 2010;MAEP, 2019;Akpatcho et al 2022), this study considers that production technologies of the farms are not homogenous. Studies found evidence that results of technical efficiency could be misleading if production technology heterogeneity is not considered (Sauer et al 2013;Bahta et al 2018). Although heterogeneity can be modelled using several methodological approaches.…”
Section: Empirical Endogenous Stochastic Production Frontier Modelmentioning
confidence: 99%
“…They also found that the determinants of inefficiency were soybean availability, production expenses, the width of the production area and the number of employees. Bahta and Baker (2015) in Botswana find an average profit efficiency of 58 percent for a sample of 556 small livestock producers in Botswana. The research showed that the factors that influenced the high degree of inefficiency (42 percent) were education level, distance to the commonly used market, herd size, access to information and income from crop production.…”
Section: Determinants Of Smes' Efficiencymentioning
confidence: 99%
“…Cattle farm sustainability can be assessed through various dimensions, including nutrient surplus, land use, greenhouse gas emissions, and animal welfare (Sturaro et al, 2012). While research on livestock sustainability, especially in small-scale beef cattle farms in developing countries, is limited (Bahta et al, 2023;Honjo et al, 1989;Ogino et al, 2016), this case-control study focused on traditional parameters. Future research should integrate modern technologies such as smart farming, precision diets, reproductive biotechnologies, molecular genetics, and animal welfare management (Greenwood, 2021;Lyles & Calvo-Lorenzo, 2014;Pulina et al, 2021;Ventura et al, 2016).…”
Section: Limitations and Future Researchmentioning
confidence: 99%